A novel mutation in CYBB induced X-linked chronic granulomatous disease: A case report. (2020) - Xu, Xuehua; Lu, Bingtai; Xie, Yaping; Yang, Diyuan; Lu, Gen; Fan, Huifeng
Abstract: Chronic granulomatous disease (CGD) is caused by gene mutations that affect the phagocyte NADPH oxidase. This results in recurrent infections by catalase-positive bacteria or fungi. Here, we report a case of X-linked CGD presenting a mixed infection with Burkholderia cepacia and Aspergillus . A novel mutation was found by bioinformatics analyses of his genealogy (c.1234 del G), which perhaps changed the structure and function of the related proteins.